Molecular cloning and functional characterization of porcine E74-like factor 4 (ELF4). (December 2016) - Shi, Yanling; Wang, Dang; Zhu, Xinyu; Wu, Qiong; Chen, Huanchun; Xiao, Shaobo; Fang, Liurong
Abstract: E74-like factor 4 (ELF4) is a novel transcription factor that initiates transcription of type I interferon (IFN) genes to control diverse pathogens. Here, porcine ELF4 (poELF4) was cloned and its role in type I IFN signaling was investigated in different porcine cell lines. Full-length cDNA of poELF4 encodes 663 amino acid residues and ectopic expression of poELF4 significantly induced IFN-β production. Interestingly, difference from the human ELF4 (huELF4), poELF4 mutants lacking the serine/threonine rich domain, which has been demonstrated to be responsible for the phosphorylation of huELF4, were still capable of activating IFN-β promoter. Using pseudorabies virus (PRV) and porcine reproductive and respiratory syndrome virus (PRRSV) as the models of DNA virus and RNA virus, respectively, we found that the replication of both PRV and PRRSV was reduced with poELF4 overexpression and enhanced with poELF4 knockdown. Taken together, these results suggested that poELF4 is an important antiviral host restriction factor. Highlights: PoELF4 is widely expressed in different tissues, especially the intestine and stomach. PoELF4 is involved in the IFN-β signaling pathway in different porcine cells. PoELF4 mutant lacking the serine/threonine rich domain still induces IFN-β expression. PoELF4 significantly inhibits the replication of both PRV and PRRSV.